Genetic Variation of the Long-Legged Flies Phacaspis mitis Complex (Diptera: Dolichopodidae) in Peninsular Thailand Inferred From Three Mitochondrial Genes. Issue 6 (13th November 2018) - Kaewkrajang, Natcha; Grootaert, Patrick; Boonrotpong, Singtoe
Abstract: Phacaspis (Meuffels and Grootaert 1988 ) is a true marine dolichopodid fly genus. They are common on the mud flats in the front of mangroves where they deal with extreme conditions. The genus is represented in southern Thailand by Phacaspis mitis (Grootaert and Meuffels 2001 ) (Diptera: Dolichopodidae). Previous studies have focused on both taxonomy and classification of this genus, but there are a few studies focusing on this species in terms of molecular genetics. The objective of the present study was to investigate genetic variation and phylogenetic relationships of P. mitis using ribosomal DNA subunit 12S, ribosomal DNA subunit 16S, and cytochrome oxidase subunit I of mitochondrial genes. The specimens were collected in six coastal provinces from the Andaman Sea and the Gulf of Thailand. The phylogenetic relationship of combined mitochondrial genes revealed that P. mitis in peninsular Thailand is a monophyletic group that can be divided into two distinct clades. According to the haplotype network, 16 haplotype patterns were observed in P. mitis, but P. mitis was separated into two major haplotype networks. In addition, a positive correlation between genetic distance ( F ST ) and geographical distance (km) was found among the populations of peninsular Thailand. The level of genetic differentiation between populations is influenced by geographic isolation. Moreover, P. mitis arose in late Eocene (35.5 Mya) and it diversified during the Plio-Pleistocene (3.14 Mya). Although, P. mitis is divided into two populations in this study, it is a well-supported monophyletic group.